1979
DOI: 10.1056/nejm197908093010601
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatinoma Syndrome

Abstract: Diabetes mellitus, steatorrhea, cholelithiasis and a tumor distorting the duodenum prompted a work-up for somatostatinoma in a 52-year-old man. The responses of pancreatic B-cells but not of A-cells to nutrient stimuli were inhibited, and growth-hormone release was suppressed, suggesting somatostatin resistance in some target tissues. Plasma somatostatin-like immunoreactivity ranged from 9000 to 13,000 pg per milliliter (normal: 88+/-8, mean +/- S.E.M.) and was distributed in four molecular forms, including fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(36 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…However, by histochemical studies no other known peptide hormone has thus far been demonstrated unambiguously to be present in pancreatic D-cells. The presence of gastrin in these cells is highly controversial , and the simultaneous production of somatostatin and calcitonin in a human tumor of the endocrine pancreas (34) has been attributed to the presence of different cell types in this tumor. On the other hand, the existence of the same prohormone in histologically different cell types and its conversion to different end products seems to be a real possibility, as evidenced from studies on the precursor of corticotropin and lipotropin in the anterior and intermediate lobes of the pituitary gland (18).…”
mentioning
confidence: 99%
“…However, by histochemical studies no other known peptide hormone has thus far been demonstrated unambiguously to be present in pancreatic D-cells. The presence of gastrin in these cells is highly controversial , and the simultaneous production of somatostatin and calcitonin in a human tumor of the endocrine pancreas (34) has been attributed to the presence of different cell types in this tumor. On the other hand, the existence of the same prohormone in histologically different cell types and its conversion to different end products seems to be a real possibility, as evidenced from studies on the precursor of corticotropin and lipotropin in the anterior and intermediate lobes of the pituitary gland (18).…”
mentioning
confidence: 99%
“…16 All these symptoms can be explained by the inhibitory actions of somatostatin in the release or action of insulin, glucagon, gastrin, secretin, somatotrophin, thyrotropin, gastric inhibitory peptide, vasoactive intestinal peptide (VIP), pancreatic polypeptide (PP), and cholecystokinin. 16,17 The patient of this report presented chronic diarrhea, cachexia, diabetes mellitus, depression, and calculous cholecystitis, which could be considered as symptoms of typical somatostatinoma syndrome. However, these symptoms seemingly were not observed together during the diagnostic process, and the diagnosis of pancreatic somatostatinoma was not taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Somatostatinoma syndrome was described 2 years after the first somatostatinoma was reported by Krejs in 1979, being more common in pancreatic somatostatinomas than in the duodenal counterpart. [16][17][18] Additional symptoms have been identified and include dyspepsia, Microscopically, the growth pattern can be solid, nested, trabecular, ribbon like, tubuloacinar, or glandular, and mixed patterns are common in the same tumor. 27,28 Psammoma bodies are commonly observed in duodenum somatostatinoma, but rarely in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
“…Tumours in which somatostatin-producing D-cells represent a majority cell type ('somatostatinomas') are rare, but have been found most often in the pancreas (Ganda et al, 1977;Larsson et al, 1977;Krejs et al, 1979;Pipeleers et al, 1979;Wright et al, 1980). The structure of the biosynthetic precursor of somatostatin (preprosomatostatin) in the human may be deduced from the nucleotide sequence of a cloned cDNA prepared from a human pancreatic tumour (Shen et al, 1982), and the structure of the gene has been determined from DNA fragments from a human genomic library (Shen & Rutter, 1984).…”
Section: Introductionmentioning
confidence: 99%